Effect of chemotherapy on hippocampal volume and shape in older long-term breast cancer survivors - Daniel, Ebenezer; Deng, Frank; Patel, Sunita K.; Sedrak, Mina S.; Young, Jonathan; Kim, Heeyoung; Razavi, Marianne; Sun, Can-Lan; Root, James C.; Ahles, Tim A.; Dale, William; Chen, Bihong T. (Frontiers in Aging Neuroscience, 2024)
Purpose: The objective of this study was to assess changes in hippocampal volume and shape in older long-term breast cancer survivors who were exposed to chemotherapy 5 to 15 years prior. Methods: This study recruited female long-term breast cancer survivors aged 65 years or older with a history of chemotherapy (C+), age-matched breast cancer survivors who did not receive chemotherapy (C-), and healthy controls (HC). The participants were recruited 5 to 15 years after chemotherapy at time point 1 (TP1) and were followed up for 2 years at time point 2 (TP2). Assessments included hippocampal volume and shape from brain MRI scans and neuropsychological (NP) tests. Results: At TP1, each of the three groups was comprised of 20 participants. The C+ group exhibited a hippocampal volume loss estimated in proportion with total intracranial volume (ICV) in both the left and right hemispheres from TP1 to TP2. Regarding the hippocampal shape at TP1, the C+ group displayed inward changes compared to the control groups. Within the C+ group, changes in right hippocampal volume adjusted with ICV were positively correlated with crystalized composite scores (R = 0.450, p = 0.044). Additionally, in C+ groups, chronological age was negatively correlated with right hippocampal volume adjusted with ICV (R=-0.585, p=0.007). Conclusion The observed hippocampal volume reduction and inward shape deformation within the C+ group may serve as neural basis for cognitive changes in older long-term breast cancer survivors with history of chemotherapy treatment.